2020
DOI: 10.1094/pdis-11-19-2345-re
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Ground-Based Air-Blast Sprayer and Aircraft Application of Fungicides to Manage Scab in Tall Pecan Trees

Abstract: Pecan scab (caused by Venturia effusa) is a destructive disease of pecan in the southeastern United States. Susceptible cultivars must be sprayed with fungicide every 10 to 21 days to ensure yield and kernel quality. Fungicide is most often applied using large orchard air-blast sprayers. Pecan trees grow tall, and air-blast sprays result in a gradient in spray deposition and consequently of scab. Aerial fungicide application is also practiced. Disease distribution and spray deposition of the two methods have n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Pesticides applied by ground-based or backpack sprayers in orchards might meet the requirements of droplet distribution in the inside and bottom part of the canopy because they are flexible to change the direction of spraying angle than UAV-based sprayers. However, a high-volume spraying method is commonly adopted when ground-based machine or knapsack are used as sprayers, which might result in significant pesticide wastes [8][9]. Furthermore, ground-based sprayers for pesticide application are subject to terrain restrictions and are labourconsuming in small or hilly orchards.…”
Section: Introductionmentioning
confidence: 99%
“…Pesticides applied by ground-based or backpack sprayers in orchards might meet the requirements of droplet distribution in the inside and bottom part of the canopy because they are flexible to change the direction of spraying angle than UAV-based sprayers. However, a high-volume spraying method is commonly adopted when ground-based machine or knapsack are used as sprayers, which might result in significant pesticide wastes [8][9]. Furthermore, ground-based sprayers for pesticide application are subject to terrain restrictions and are labourconsuming in small or hilly orchards.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study confirmed that water-sensitive spray cards can be used to obtain spray coverage data in the strawberry canopy, and also identified nozzle height above the canopy, spray volume, and pressure as important factors that affect spray coverage [41]. In addition, there are numerous studies in which water-sensitive spray cards have been used to describe spray coverages in orchard crops [2,[42][43][44][45]. Under favorable spray application conditions, i.e., high temperature, low wind, and low ambient relative humidity, spray coverage patterns on water-sensitive spray cards typically show a clear distinction between blue/purple spray droplets and the background (yellow spray card) (Figure 2a,b).…”
Section: Water-sensitive Spray Cards To Quantify Spray Coveragementioning
confidence: 90%
“…An air-assisted spraying system could improve the pesticide deposit levels and the coverage rate on leaves, increase the penetration of the spray droplets into the canopy and reduce the spray loss. 4 Many tractor operated air-assisted sprayers were developed for the height of 15 m for better deposition and coverage of pesticide throughout the canopy 5 , 6 but very limited work has been reported in the air assisted sprayers above 15 m for tall crops like coconut field. 7 9 Arecanut ( Areca catechu L.) is a profitable plantation crop widely grown in India and Tropical Asia.…”
Section: Introductionmentioning
confidence: 99%